Trends and influencing factors of HIV health education receive rate among 0.57 million migrants in China from 2009 to 2017: a national population-based study - Yue Che; Jun Wang; Chao Song; Xueyao Wang; Yang Bai; Jue Liu (BMC, 2023)
Abstract Introduction China has implemented Basic Public Health Service (BPHS) in 2009, aiming to improve the health status of the people, and the content of service includes implying health education for residents. As an important group of people, the migrants can easily become main reason for major infectious diseases such as HIV between different provinces, but the effect of receiving health education is still unknown for migrants. Therefore, the health education of China's migrant population has received widespread attention. Methods This study used the data of the China Migrants Dynamic Survey (CMDS) from 2009 to 2017, and evaluated the trend of HIV health education acceptance rate of different migrant groups across the country (n = 570,614). Logistic regression model was used to test the influencing factors of HIV health education rate. Results: The study found that the overall HIV health education rate of Chinese migrants decreased from 2009 to 2017, and different types of migrants showed different trends. The proportion of migrants aged 20-35 who receive education fluctuates, and ethnic minorities, western regions, and migrants with high education were more likely to receive HIV health education. Conclusion: These findings identify when implementing health education for migrants, we can carry out more education for specific groups to promote the health equity of the migrant population.